2020
DOI: 10.1016/j.scitotenv.2020.140680
|View full text |Cite
|
Sign up to set email alerts
|

Snowballing transmission of COVID-19 (SARS-CoV-2) through wastewater: Any sustainable preventive measures to curtail the scourge in low-income countries?

Abstract: The potential risks of COVID-19 in wastewater are highlighted. • Wastewaters from hospitals, quarantine centers, etc. dedicated to COVID-19 treatments may contain SARS-CoV-2 RNA particles. • Preventive measures to tackle the potential risks of SARS-CoV-2 transmission in wastewater are proposed. • Chlorination, ozonation, and UV radiations are useful in SARS-CoV-2 deactivation in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 56 publications
2
102
0
1
Order By: Relevance
“…This suggests that there may be other potential routes of transmission, such as exposure to SARS-CoV-2 that survive in community environment. Given that the infectious SARS-CoV-2 was found to be secreted through the human urinary system ( Sun et al, 2020 ) and intestinal tract ( Wang et al, 2020d ; Xiao et al, 2020b ; Zhou et al, 2020a ), and SARS-CoV-2 RNA was detected in wastewater worldwide ( Randazzo et al, 2020 ), many studies have suggested the possibility of wastewater transmission of COVID-19 disease ( Adelodun et al, 2020 ; Arslan et al, 2020 ; Foladori et al, 2020 ). However, the direct use of untreated excreta as a fertilizer and the flushing of excreta from open cesspools into the waters on rainy days might lead to serious water pollution, including the SARS-CoV-2 within human excreta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that there may be other potential routes of transmission, such as exposure to SARS-CoV-2 that survive in community environment. Given that the infectious SARS-CoV-2 was found to be secreted through the human urinary system ( Sun et al, 2020 ) and intestinal tract ( Wang et al, 2020d ; Xiao et al, 2020b ; Zhou et al, 2020a ), and SARS-CoV-2 RNA was detected in wastewater worldwide ( Randazzo et al, 2020 ), many studies have suggested the possibility of wastewater transmission of COVID-19 disease ( Adelodun et al, 2020 ; Arslan et al, 2020 ; Foladori et al, 2020 ). However, the direct use of untreated excreta as a fertilizer and the flushing of excreta from open cesspools into the waters on rainy days might lead to serious water pollution, including the SARS-CoV-2 within human excreta.…”
Section: Resultsmentioning
confidence: 99%
“…As excreta was directly used as fertilizer, fruits and vegetables grown in rural areas might be contaminated by SARS-CoV-2 and then eaten by wild animals, or purchased and eaten by rural and urban residents through wet markets. Long-term exposure to contaminated environmental sources, such as the air pollutants, extended exposure to aerosols produced by contaminated water, and the inadequate cleaning processes of food and the surfaces of some materials, may resulted in an increased risk of SARS-CoV-2 transmission ( Adelodun et al, 2020 ; Carraturo et al, 2020 ). Thus, it was seemly reasonable that the SARS-CoV-2 survives in nature could be a potential sustainable source of infection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The wastewater treatment ponds are most applied in rural and developing countries, which need more than two weeks to get reduction one log of viruses [91] . Therefore, if the wastewater and waste from these underdeveloped regions was not treated properly, it would result in snowballing transmission of COVID-19 in wastewater, as seen in other viral diseases previously [92] , [93] .…”
Section: Characteristics Of Coronaviruses In Aqueous Environmentmentioning
confidence: 99%
“…• 409 • (DI MARIA et al, 2020). Because of the many pathways of the SARS-CoV-2 spread, the virus can be transmitted in water systems, main those that receive untreated wastewater from hospitals and communities, that play a pivotal role of the potential vehicle for contamination (ADELODUN et al, 2020). The sewage sludge is a reservoir for the novel coronavirus due to the organic matter that can support the virus and the potential risk of transmission (YANG et al, 2020).…”
Section: Saúde E Ambientementioning
confidence: 99%
“…Water quality maintenance and proper sanitation confers benefits for people and can contribute to the prevention of SARS-CoV-2 transmission, policies must assure that adequate compliance of wastewater discharge during the pandemic of COVID-19, including surveillance in rural areas and small villages (ADELODUN et al, 2020). The use of contaminated water for consumption and cleaning…”
Section: Saúde E Ambientementioning
confidence: 99%